Study on degradation behavior of commercial 18650 LiAlNiCoO2 cells in over‐charge conditions. (20th November 2018) - Kong, Depeng; Wen, Ruoxi; Ping, Ping; Peng, Rongqi; Zhang, Jiaqing; Chen, Guoming
Summary: From the battery life and safety perspective, an investigation was conducted to analyze the degradation behavior of 18650 LiAlNiCoO2 (NCA/C) cells with different cut‐off voltages (4.30, 4.50, 4.80 and 5.00 V) and different cycle numbers. Electrochemical Impedance Spectroscopy (EIS) and Incremental Capacity (IC) analysis were employed to identify the fading mechanism for overcharged NCA/C cells. Key insights were that major side reactions for the overcharged NCA cells are the oxidation and decomposition of electrolyte, the thickening of the passivation layer, the deposition of lithium and the structure change of cathode. These side reactions accounted for the increase of impedance for the cells with the cut‐off voltages and the cycle numbers, especially for the charge transfer impedance. An EIS‐distribution of relaxation time (DRT) method was applied to identify and quantify the influences of various degradation modes during overcharging process. The loss of lithium inventory (LLI) was more pertinent to the degradation than the conductivity loss (CL) and the loss of active material (LAM). Conspicuous variations in the cell can assist in self‐test and failure warning, such as the rapid rise of the temperature change rate, the evident transformation of peaks in IC results and the irreversible increase of CL. Abstract : Electrochemical Impedance Spectroscopy and Incremental Capacity analysis were employed to identify the fading mechanism for overcharged NCA/C cells. Side reactions accounted for the increase of impedance for the cells with the cut‐off voltages and the cycle numbers, especially for the charge transfer impedance. Conspicuous variations in the cell can assist in self‐test and failure warning.